Synergistic Radioprotection by Gamma-Tocotrienol and Pentoxifylline: Role of cAMP Signaling. (7th July 2013) - Kulkarni, Shilpa; Chakraborty, Kushal; Kumar, K. Sree; Kao, Tzu-Cheg; Hauer-Jensen, Martin; Ghosh, Sanchita P.
Abstract : Purpose . This study was designed to determine the efficacy and mechanisms of radioprotection by the combination of gamma-tocotrienol (GT3) and pentoxifylline (PTX) against acute radiation injury. Materials and Methods . Post-irradiation survival was monitored to determine the most efficacious dose and time of administration of PTX. Dose reduction factor (DRF) was calculated to compare the radioprotective efficacy of the combination. To determine the mechanism of synergistic radioprotection by the combination, mevalonate or calmodulin were coadministered with the GT3-PTX combination. Mevalonate was used to reverse the inhibitory effect of GT3 on 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR), and calmodulin was used to reverse the inhibition of phosphodiesterase (PDE) by PTX. Results . The combination was most effective when 200 mg/kg of PTX was administered 15 min before irradiation along with 200 mg/kg of GT3 (−24 h) and resulted in a DRF of 1.5. White blood cells and neutrophil counts showed accelerated recovery in GT3-PTX-treated groups compared to GT3. Mevalonate had no effect on the radioprotection of GT3-PTX; calmodulin abrogated the synergistic radioprotection by GT3-PTX. Conclusion . The mechanism of radioprotection by GT3-PTX may involve PDE inhibition.